Methylation of the epigenetic JMJD2D protein by SET7/9 promotes prostate tumorigenesis - Gu, Ruicai; Kim, Tae-Dong; Jiang, Hanlin; Shin, Sook; Oh, Sangphil; Janknecht, Ralf (Frontiers in Oncology, 2023)
How the function of the JMJD2D epigenetic regulator is regulated or whether it plays a role in prostate cancer has remained elusive. We found that JMJD2D was overexpressed in prostate tumors, stimulated prostate cancer cell growth and became methylated by SET7/9 on K427. Mutation of this lysine residue in JMJD2D reduced the ability of DU145 prostate cancer cells to grow, invade and form tumors and elicited extensive transcriptomic changes. This included downregulation of CBLC, a ubiquitin ligase gene with hitherto unknown functions in prostate cancer, and upregulation of PLAGL1, a transcription factor with reported tumor suppressive characteristics in the prostate. Bioinformatic analyses indicated that CBLC expression was elevated in prostate tumors. Further, downregulation of CBLC largely phenocopied the effects of the K427 mutation on DU145 cells. In sum, these data have unveiled a novel mode of regulation of JMJD2D through lysine methylation, illustrated how this can affect oncogenic properties by influencing expression of the CBLC gene, and established a pro-tumorigenic role for CBLC in the prostate. A corollary is that JMJD2D and CBLC inhibitors could have therapeutic benefits in the treatment of prostate and possibly other cancers.